Prevalence of multiple sclerosis in Verona, Italy: an epidemiological and genetic study. Issue 4 (24th December 2012) - Gajofatto, A.; Stefani, A.; Turatti, M.; Bianchi, M. R.; Lira, M. G.; Moretto, G.; Salviati, A.; Benedetti, M. D.
<x xml:space="preserve">Abstract</x> Background and purpose Recent multiple sclerosis (MS) prevalence studies classify Italy as a high‐risk area without intra‐regional latitude effect. Objectives To determine MS prevalence in Verona, Italy, and frequency of myelin oligodendrocyte glycoprotein (MOG) gene G511C polymorphism and HLA‐DRB1*15 locus in a sample of cases and healthy controls. Methods The study area population on the prevalence date (31 December 2001) was 253 208 (133 508 women, 119 700 men). Multiple case sources were examined. Patients fulfilling McDonald's criteria (2001) were included. Crude, age‐ and sex‐specific prevalence rates were computed. MOG G511C polymorphism and HLA‐DRB1*15 were determined by standard methods. Results We identified 270 cases of MS yielding a crude prevalence rate of 106.6/100 000 (95% CI: 94–120). Prevalence was higher in women (140.8/100 000) than in men (68.5/100 000). The age‐adjusted prevalence rate standardized to the European population was 96.0/100 000. MOG G511C polymorphism did not differ between cases and controls. HLA‐DRB1*15 frequency was 58/155 (37%) in cases and 24/157 (15%) in controls (P < 0.001). There was no HLA‐DRB1*15 influence on susceptibility to other autoimmune disorders. Conclusions The high MS prevalence in Verona confirms Italy as a high‐risk area with a homogenous distribution across the country. HLA‐DRB1*15 is a relevant MS susceptibility locus in the Italian population, possibly with little influence on the occurrence of concomitant autoimmune disorders.